Pengaruh Lama Penggunaan Gadget Dengan Perkembangan Anak di TK MDI I Plus - Uswatun Qoyyimah, Anna; Wahyuni, Sri; Hartati, Lilik; Dynamurti Wintoro, Piscolia (INVOLUSI: Jurnal Ilmu Kebidanan, 2025)
Gadgets are small electronic devices that have specific functions, such as smartphones, iPhones, handphones, BlackBerrys, netbooks, tablets, and similar devices. In addition, gadgets significantly impact human lifestyles in terms of thinking patterns, feelings, and behaviors. The use of gadgets in daily life can affect adults, but children are also not exempt from these effects. Gadgets are tools or media used for social interaction, particularly for social contact and communication.The purpose of this research is to examine the effect of the duration of gadget use on the development of children at TK MDI I Plus. The research design is quantitative with a cross-sectional approach. The study was conducted at TK MDI I Plus in Pandeyan Village, Ngemplak District, Boyolali, with a sample of 45 respondents. The measuring instruments used are questionnaires and the Denver II, with the aim of using the questionnaire to assess the intensity of gadget use among early childhood. Data analysis includes univariate and bivariate analysis with the Chi-square test.The results show that among the 45 preschool respondents studied at TK MDI I Plus, 80% are high-intensity gadget users. The number of children with normal development in the high category is 26.7%, and those classified as suspect is 73.3%. From the data analysis results, the obtained p-value is 0.000, which is less than 0.05. The conclusion indicates a significant effect of the duration of gadget use on the development of children at TK MDI I Plus. Keywords: Duration of gadget use, child development